2008
DOI: 10.1897/08-016.1
|View full text |Cite
|
Sign up to set email alerts
|

Chemical availability and sediment toxicity of pyrethroid insecticides to Hyalella azteca: Application to field sediment with unexpectedly low toxicity

Abstract: Tenax extraction is a simple, inexpensive approach to estimate the bioavailability of hydrophobic organic contaminants from sediment. In the present study, a single-point Tenax extraction was evaluated regarding its correlation with the acute toxicity to Hyalella azteca using field-collected sediments in California, USA. Pyrethroids were believed to be the primary contributor to the observed toxicity, and a significant correlation existed between the expected toxicity (given pyrethroid concentrations) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
10

Relationship

8
2

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 28 publications
3
65
0
Order By: Relevance
“…Similar to the current study, SPs have been frequently detected in sediments from California (Amweg et al, 2006;Holmes et al, 2008;Trimble et al, 2009;You et al, 2008;Weston et al, 2004Weston et al, , 2005, Texas (Hintzen et al, 2009), and Illinois (Ding et al, 2010) in USA, as well as the PRD in China . The OPs, however, were detected at lower frequencies and concentrations in those studies.…”
Section: Comparison To Other Studiessupporting
confidence: 87%
“…Similar to the current study, SPs have been frequently detected in sediments from California (Amweg et al, 2006;Holmes et al, 2008;Trimble et al, 2009;You et al, 2008;Weston et al, 2004Weston et al, , 2005, Texas (Hintzen et al, 2009), and Illinois (Ding et al, 2010) in USA, as well as the PRD in China . The OPs, however, were detected at lower frequencies and concentrations in those studies.…”
Section: Comparison To Other Studiessupporting
confidence: 87%
“…A similar finding has previously been reported with some sediments having high Spyr-TUs, but unexpectedly low toxicity to H. azteca (Amweg et al, 2006;Kuivila et al, 2012;You et al, 2008). Due to the limited data on sediment toxicity to H. azteca in China, the present dataset was compared to the data reported from the United States (Amweg et al, 2006;Kuivila et al, 2012;Ng et al, 2008;Weston et al, 2004Weston et al, , 2005Weston et al, , 2008a (Fig.…”
Section: Overestimation Of Toxicity By the Traditional Tu Approachsupporting
confidence: 77%
“…A similar phenomenon has been reported before Environmental Science & Technology ARTICLE and low bioavailability of sediment bounded pyrethroids explained the low observed toxicity. 30 Recent studies 8,31 have shown that bioavailability of hydrophobic contaminants to benthic species from sandy sediments which had extremely low TOC content, were lower than that estimated from their TOC-normalized concentrations because of their possible binding to the inorganic components in sediment. Sediment GZ8 had an extremely low TOC of 0.53% and may exhibit a lower than expected toxicity.…”
Section: Articlementioning
confidence: 99%